Photosynthetic complex stoichiometry dynamics in higher plants: environmental acclimation and photosynthetic flux control - Schöttler, Mark A.; Tóth, Szilvia Z. (Frontiers in Plant Science, 2014)
The composition of the photosynthetic apparatus of higher plants is dynamically adjusted to long-term changes in environmental conditions such as growth light intensity and light quality, and to changing metabolic demands for ATP and NADPH imposed by stresses and leaf ageing. By changing photosynthetic complex stoichiometry, a long-term imbalance between the photosynthetic production of ATP and NADPH and their metabolic consumption is avoided, and cytotoxic side reactions are minimized. Otherwise, an excess capacity of the light reactions, relative to the demands of primary metabolism, could result in a disturbance of cellular redox homeostasis and an increased production of reactive oxygen species, leading to the destruction of the photosynthetic apparatus and the initiation of cell death programs. In this review, changes of the abundances of the different constituents of the photosynthetic apparatus in response to environmental conditions and during leaf ontogenesis are summarized. The contributions of the different photosynthetic complexes to photosynthetic flux control and the regulation of electron transport are discussed.